the Ultrasound Findings of Mammographically Dense Breasts in A Sample of Iraqi Female Patients - khaleel Mohson (مجلة كلية الطب, 2019)
Background: breast problems including breast cancer are increasing in Iraq during the recent years, yet, early detection and screening programs using mammography mainly with complementary ultrasound had dramatically decreased the mortality rates from this emerging disease.